(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Annona muricata (AMC), is a tropical plant species of the Annonaceae family known for its medicinal uses in ameliorating and/or protecting several organs and tissues in the body. In this study we elucidated the influence of the methanol extracts of AMC leaf and stem bark on the biochemical and histological integrity of the colorectum. Different doses (100, 200, 400, 600, and 800mg of extract/kg body weight) of methanol extracts of the leaves and stembark were orally administered to adult male Wistar rats of average weight (100 - 150 g) for 28 days. At the end of the experimental period, the rats were sacrificed and colorectal tissues harvested for analyses. Adenosine triphosphatase (ATPases), lactate dehydrogenase (LDH), glucose-6-phosphate dehydrogenase (G6PD) activities, and tissue protein (TP) concentration, were evaluated by colorimetric method using appropriate test kits. The results in the colorectal tissue analysed showed that total ATPase, LDH and G6PD (energy markers) activities increased significantly in the groups which received methanol leaf and stem bark extracts of AMC when compared with control. However, a general decrease was observed in TP and Na+/K+-ATPase activity but there was a twist in Na+/K+-ATPase activity in stem bark doses of 200mg/kg and 400mg/kg which showed significant increases in dose dependent manner when compared with the control. Even though G6PD activity showed fluctuating patterns for both extracts, the highest dose (800mg/kg) reflected the most significant increase when compared with the control. The histology confirmed the toxicological results by the biochemical parameters. Under the condition of this study, we inferred that the methanol leaf and stem-bark extracts of AMC may significantly influence the enzymes by reducing and increasing total ATPase and Na+/K+-ATPase activities depending on the doses and administration should therefore depend on the desired outcome.